Teologia e ciências sociais (Theology and Social Sciences) - DOI: 10.5752/P.2175-5841.2012v10n28p1337 - Júnior, Francisco de Aquino (2012)
This article presents the issue of the relationship between theology and the social sciences. For this purpose, the author seeks to formulate the terms of the relationship of these two areas of Knowledge, highlighting the importance, the role and the place of the social sciences in the development of the theological discourse and of the theological product. At the beginning of the text the author presents a discussion on the relationship between theology and the social sciences in Latin America in recent decades through its main representatives: Gustavo Gutierrez and Clodovis Boff, Juan Luis Segundo and Ignacio Ellacuria. The paper also presents a systematic outline of the fundamental theoretical framework of the relationship between theology and the social sciences, showing that this relationship binds to the knowledge of the reality in which faith is placed. In conclusion, the texts highlights that faith must be considered theologically on three levels: with the social dimension of the Kingdom of God, which is an issue of Christian Theology; with the social character of theology as a theory; with the ideological suspicion and with the process of liberation of theology.
O artigo se confronta com a problemática da relação entre teologia e ciências sociais. Sua pretensão é formular adequadamente os termos dessa relação, explicitando a importância, a função e o lugar das ciências sociais na elaboração do discurso teológico e no produto teológico. Começa apresentando o debate sobre a relação entre teologia e ciências sociais na América Latina nas últimas décadas através de seus principais interlocutores: Gustavo Gutiérrez e Clodovis Boff; Juan Luis Segundo e Ignácio Ellacuría. E conclui, esboçando, de modo sistemático, ainda que em forma de tese, a estrutura teórica fundamental dessa relação. Ela tem a ver com o conhecimento da realidade na qual se vive a fé e que deve ser pensada teologicamente; com a dimensão social do reinado de Deus, assunto da teologia cristã; com o caráter social da teologia, enquanto teoria; e com a suspeita ideológica e o processe de des-ideologização e libertação da teologia.
Keywords: Mediação; Ciências Sociais; Teologia; Social